DIVERSIFICATION OF PROCESSED RAMBUTAN PRODUCTS AS AN EFFORT TO INCREASE THE INCOME OF THE SOKKOLIA VILLAGE COMMUNITY - Andi Asmawati Azis; Zakia Asrifah Ramly; Nani Kurnia; Kusdianawati Kusdianawati; Muhammad Isrul; Agam Aslam Adigama (Universitas Negeri Makassar, 2026)
Sokkolia Village, Gowa Regency, has high agricultural potential, especially rambutan fruit, yet its utilization is still limited to selling fresh fruit with low economic value. This community service program aimed to improve community knowledge and skills in processing rambutan into superior village products to support local economic development. The implementation methods included preliminary surveys, socialization, rambutan processing training, packaging and branding assistance, and program evaluation. The resulting products included rambutan syrup, jam, and candied rambutan with more attractive packaging and higher selling value. The results showed significant improvement in community knowledge regarding product value addition, processing skills, production sanitation, marketing, and entrepreneurial interest. Community enthusiasm during the program also indicated strong potential for developing local commodity-based businesses. This program proves that transforming rambutan into processed products can be an effective strategy for creating superior village products and increasing community income. Continuous assistance is needed so that rambutan-based businesses can grow independently and sustainably.